Estimating epidemiological data of Multiple sclerosis using hospitalized data in Shandong Province, China. Issue 1 (December 2016) - Liu, Xiao; Cui, Yazhou; Han, Jinxiang
Abstract Background Multiple sclerosis (MS) is a rare chronically debilitating disease. There are few reports on the burden of disease of MS and prevalence in China. The authors intended to estimate disease burden and prevalence of MS in Shandong Province using available epidemiologic data. Methods Prevalence was calculated using DISMOD II software based on incidence extrapolated from hospitalization data, case fatality and remission rate from literature as input indexes. Disability-adjusted life year (DALY) was computed with epidemiologic indexes estimated by DISMOD II program. Results The prevalence of MS was estimated to be 3.7(95 % CI: 1.65–5.8) and 6.7(95 % CI: 2.7–9.56) cases per 100, 000 people for males and for females, respectively. The mean age at onset of MS was 36.0(43.0 ± 30.0 years in males and 33.7(43.4 ± 29.7) years in females. Duration of the disease was estimated to be 34.0 (31.6 ± 21.0) years for males and 39.5(34.9 ± 21.8) years for females. The disease burden in disability-adjusted life years was 3316, comprised of 903 (27.2 %) years of life lost (YLL) and 2413 (72.8 %) years lived with disability (YLD). Conclusions Our study highlighted that population in Shandong Province had a high prevalence of MS and the patients had a heavy disease burden. It also revealed that the results obtained in this paper would be useful to provide a reference for establishing specific healthcare policies for this rare disease in Shandong Province.